Use of Arduino and flute in teaching waves in a high school class - Nunes, Jade Barbosa; Admiral, Tiago Destéffani (Brazilian Journal of Science, 2024)
This work aims to use music as a teaching tool and, alongside it, utilize Arduino as a device to verify the components to be studied. The theoretical framework to be used is based on the Potentially Meaningful Teaching Units, UEPS approach, allowing for the construction of meaningful learning for students through problem-solving situations. A didactic sequence was developed for the study of the theme of sound waves and their components at the high school level. This sequence was applied over a period of four weeks, including an initial presentation of topics related to waves, the construction of an electronic system using Arduino, and the verification of phenomena based on musical notes. The data collection instruments for this research included questionnaires to assess students’ prior knowledge, mind maps, and exercise lists. The Arduino programming board, which allows for the digitization of analog and digital electrical signals, was used in conjunction with a microphone module, enabling the integration of electronic physics with wave physics. As a result of this research, there were indications of learning through the interdisciplinary relationship between music and physics, which was made effective through the use of Arduino and the recorder flute.